PENGARUH SELF-ATTRIBUTION BIAS DAN RISK PERCEPTIONS TERHADAP PENGAMBILAN KEPUTUSAN INVESTOR PASAR MODAL : Studi pada Kebijakan Prosentase ARB 15% Oleh Bursa Efek Indonesia - Kusumawardani, Anisa; Rahmadhani, Sari; Praptitorini, Mirna Dyah; Kase, Ratna (Jurnal Riset Manajemen dan Akuntansi, 2023)
The high amount of capital market investors during the Covid-19 pandemic and the decline in this amount when the Covid-19 pandemic ended made stock prices on the Indonesian capital market fluctuate actively. This prompted policy makers to issue new regulations of Auto Rejection Bawah (ARB) in 15%. This makes the psychology of investors when making investment decisions in the capital market may change. This study tries to see the effect of self-attribution bias and perceived risk as a factor of behavioral finance on capital market investment decision making when the 15% ARB is applied. The data of the study used 45 respondents as investors in the Indonesian capital market and processes them using multiple linear regression through SPSS 25. The results show that there is no effect of self-attribution bias and perceived risk on capital market investment decision making when the 15% ARB is applied. The implication of this research is to provide knowledge about psychological factors that occur when making decisions, especially in the capital market.